Fully Vacuum‐Processed Perovskite Solar Cells on Pyramidal Microtextures. Issue 1 (17th November 2020) - Gil-Escrig, Lidón; Roß, Marcel; Sutter, Johannes; Al-Ashouri, Amran; Becker, Christiane; Albrecht, Steve
Abstract : Solar cells based on metal halide perovskites have attracted tremendous attention due to the rapid increase in performance of single junctions and tandem solar cells. Recently, highest perovskite/silicon tandem efficiencies are realized with front‐side polished silicon wafers or adapted microstructure of textured silicon solar cells. One way to integrate perovskite top cells on typical micrometer‐sized pyramidal structures, is conformal vacuum‐based perovskite deposition. Herein, fully vacuum‐based perovskite solar cells are developed on top of random pyramidal microtextured glass substrates with a pyramid size up to 9 μm. This method allows improvement of the light management of the textured perovskite solar cell and resembles the typical pyramid topography of silicon solar cells as a step toward monolithic tandem integration. Moreover, to improve the quality of the perovskite on the textured substrates, three different methylammonium lead iodide (MAPbI3 ) films are tested by adjusting the rate ratio of the precursors. Optimized ratios for textured substrates with higher PbI2 rates enable a transient photoluminescence decay time above 0.75 μs approaching that of planar substrates at around 1.2 μs. Finally, a efficiency over 15% is achieved, which is, to the best of our knowledge, the first reported device on microscopically textured glass by co‐evaporated ion. Abstract : Vacuum‐based perovskite solar cells are developed on random pyramidal microtextured glass. This improves light management and resembles the typical topography of silicon solar cells for monolithic tandem integration. Optimized precursor rate ratios enable high charge carrier lifetimes and proper film morphology on texture. This results in >15% efficiency and the first reported perovskite solar cell on microscopically textured glass by evaporation.